S&T/R&D - Medium-Term National Action Agenda for Productivity (MNAAP) - Caesar B. Cororaton (Philippine Institute for Development Studies (PIDS), 2000)
The paper looks into the S&T/R&D-MNAAP by examining whether the strategies, programs and activities set are able to address the real issues surrounding the S&T sector. The paper discusses the major insights drawn from the recent study conducted by PIDS on R&D and compares these with the programs in the MNAAP to see whether they do address the major gaps in the sector. Generally, it was observed that the recently formulated strategies and programs in the MNAAP on S&T/R&D may not be able to adequately address the structural deficiencies in the sector. These structural deficiencies in (a) leadership, focus, and direction; (b) organization of the sector; (c) inefficiencies in the structure of incentives and allocation of R&D resources, present a set of stumbling blocks that may prevent and hinder any new set of programs and activities from attaining the goals set in the S&T/R&D-MNAAP. Major structural reforms may be needed before meaningful programs and funding requirements are set.
Keywords: 330; productivity; science and technology; Technologiepolitik; Technologiepolitik; Industrieforschung; Produktivität; Philippinen